Differences in Jurisprudential Opinion During the Era of the Companions, may Allah Pleased them all (Islamic Sciences Journal, 2024)
This research,  entitled (Differences of Jurisprudential Opinion during the Era of the Companions), studies the established and frequently reported jurisprudential differences from the Companions of the Messenger of Allah, may Allah bless him and grant him peace. Their differences are considered the cornerstone of the differences of scholars and imams who came after them.      Understanding the differences of the Companions helps in understanding and digesting the differences of others who came after their era. From this standpoint, this research addresses this issue through three branches: In the first section, the discussion is about the group that bore the responsibility of conveying the message and the Sharia after the death of the Messenger, may Allah bless him and grant him peace, while in the second section their differences are documented by presenting examples of famous issues in which they differed among themselves.  In the third section the reality of the fundamental reasons that led to  the disagreement occurred between them and then it spreads to those after them.
Keywords: Endurance, companions, differences, reasons, legislative texts.